2012
DOI: 10.1590/s1984-82502012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Compression and evaluation of extended release matrix pellets prepared by the extrusion/spheronization process into disintegrating tablets

Abstract: In this study, a novel approach for compression of matrix pellets into disintegrating tablets has been studied in an attempt to overcome the issues pertaining to rupture of polymer coat during compression of reservoirtype pellets. Extended release matrix pellets were prepared by the extrusion/spheronization technique using commercially available aqueous dispersions of ethyl cellulose, acrylic polymers and sodium alginate at 10%, 20% and 30%w/w levels. Sertraline hydrochloride was used as the model drug and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The post compression study includes thickness, hardness, friability, weight variation and assay are found in the range specified 23,24,25 ; the data are tabularized in Table 6. …”
Section: Evaluation Of Tablets For Post Compression Propertiesmentioning
confidence: 99%
“…The post compression study includes thickness, hardness, friability, weight variation and assay are found in the range specified 23,24,25 ; the data are tabularized in Table 6. …”
Section: Evaluation Of Tablets For Post Compression Propertiesmentioning
confidence: 99%
“…Compression of pellets is a major challenge which involves segregation of pellets in hopper as well as on turret. Turret speed may lead to segregation of pellets which may have impact on final DP-CQA's Assay, drug release and content uniformity of tablets 3,4 . Other factors that may have impact on DP-CQAs are size, shape and density of pellets, nature of polymer and polymer coating, amount of polymer coating and nature and amount of extra-granular excipients 5-8.…”
Section: Introductionmentioning
confidence: 99%